Analytical model for quick assessment of capillary storage capacity in saline aquifers. (October 2017) - Zhu, Langtao; Liao, Xinwei; Chen, Zhiming; Mu, Lingyu; Chen, Xuyang
Highlights: A relative permeability curve analysis method is developed to assess the capillary storage capacity. Capillary snap-off trapping mechanism is found to have strong influence on the capillary storage capacity. Greater mutual solubility factor leads to a higher capillary sequestration capacity. Effects of some critical parameters on capillary storage capacity have been investigated. Abstract: This paper initially presents a new quick and reasonable analytical method, derived from the relative permeability curves, to estimate the capillary storage capacity of saline brine aquifers. In this model, the effect of CO2 dissolution in formation brine and the hysteresis effect of gas-alternating-water injection process are considered. Firstly, a five-region seepage model for a vertical injection well is proposed in consideration of multi-phase flow, mutual solubility of CO2 and water in the aqueous and gaseous phases, and capillary trapping mechanism. Then, combined with Buckley–Leverett fractional flow and quasi-steady state theories, the five-region seepage model is solved and the saturation profile is obtained. Finally, with the solution of saturation profile, the capillary trapping capacity of saline brine aquifers can be easily estimated at different relative permeability curves. To validate the new proposed approach, a real saline brine aquifer is studied and numerical validation is conducted. In addition, based on the real case, the effect of some key factors on capillary storage capacity are studied through sensitivity analysis.